The status of the Prime Minister in the sphere of security - Mirosław Karpiuk; Marek Klimek (Journal of Modern Science)
Objectives The purpose of this article is to analyse legal regulations defining the status of the Prime Minister in the sphere of both internal security and external security of the state, and also to characterise and systematise the Chairperson’s tasks and competences which concern preventing and combating threats, as well as mitigating their consequences.